Methodological Approaches to Societies in Transformation How to Make Sense of Change - Berriane, Yasmine; Derks, Annuska; Kreil, Aymon; Lüddeckens, Dorothea (Anthropology, Change, and Development,, 2021)
Carefully contextualizing the ethnography by taking scale and time seriously, the book shows why fieldwork is both necessary and insufficient if the aim is to make sense of the contemporary world. It is a significant contribution to the renewal of anthropological theory and methodology. Highly recommended! -Thomas Hylland Eriksen, University of Oslo, Norway With an eye for various scales, biographies of people and things, and processes as they take place, this book provides insights into how, to whom, and when things change, how it feels like - and also how some things stay the same. -Samuli Schielke, Leibniz-Zentrum Moderner Orient (Berlin) This important book, drawing on ethnographic research from across the globe, addresses both the 'why' and the 'how' of studying societal change, inviting the reader to reflect on the potential - and the limits - of qualitative methods. -Jonathan Rigg, University of Bristol, UK This open access book provides methodological devices and analytical frameworks for the study of societies in transformation. It explores a central paradox in the study of change: making sense of change requires long-term perspectives on societal transformations and on the different ways people experience social change, whereas the research carried out to study change is necessarily limited to a relatively short space of time. This volume offers a range of methodological responses to this challenge by paying attention to the complex entanglement of qualitative research and the metanarratives generally used to account for change. Each chapter is based on a concrete case study from different parts of the world and tackles a diversity of topics, analytical approaches, and data collection methods. The contributors' innovative solutions provide valuable tools and techniques for all those interested in the study of change. Yasmine Berriane is permanent researcher at the French National Center for Scientific Research (CNRS, Centre Maurice Halbwachs), France. Annuska Derks is Associate Professor in the Department of Social Anthropology and Cultural Studies at the University of Zurich, Switzerland. Aymon Kreil is Assistant Professor in the Department of Languages and Cultures at Ghent University, Belgium. Dorothea Lüddeckens is Professor in the Department of Religious Studies at the University of Zurich, Switzerland.